Development and Usability Testing of an Emergency Alert Device for Elderly People and People with Disabilities - Suchitporn Lersilp (2020)
© 2020 Suchitporn Lersilp et al. The objectives of this study were to develop and evaluate the effectiveness of an emergency alert device for elderly people and people with disabilities by usability testing. There were two phases in this study: (1) development of a prototype for an emergency alert device and (2) usability testing of the device. Results presented development of the prototype, which comprised parts for sending and receiving signals. There were two kinds of alarms for emergency calls known as conscious and unconscious alerts. Participants in the usability testing phase included 12 specialists and 161 users that comprised 146 elderly people or people with disabilities and 15 caregivers or community health volunteers. The instruments used were a rating scale, usability checklist, and individual interviews regarding the usability, general appearance, and use of the device. The users agreed with the overall aspects regarding usability of the device, its general appearance, and use (X ± SD = 4.24 ± 0.88, 4.11 ± 0.90, and 4.37 ± 0.83, respectively). Most of the participants, both specialists and users, gave their perspectives on improving the size, color of the letters displayed, type of wristband, and method for sending signals.